FAKTOR-FAKTOR YANG MEMPENGARUHI KURANGNYA MINAT MAHASISWA DEPARTEMEN MATEMATIKA UNIVERSITAS NEGERI PADANG MENGIKUTI ORGANISASI MAHASISWA MENGGUNAKAN ANALISIS FAKTOR - Hidayat, Ryan; Murrni, Dewi (Journal of Mathematics UNP, 2023)
Student organizations are one of the educational shelters on campus in order to prepare students to implement their skills and knowledge in society. In this research, the purpose is to see at the factors that impact students' lack of interest in joining student organizations. This research type was applied research. The research population is Mathematics Department students of UNP class 2018-2020 who did not take part in student organizations during the July-December 2021 semester lectures. The technique for sampling used was stratified random sampling. Data obtained through the distribution of questionnaires which were analyzed using factor analysis. Our findings indicate that these factors are composed of two factors, that were, the main factor is caused by environmental, psychological, and situational variables and the second factor is caused by family and time variables